Analisis Qanun (Lembaga Keuangan syariah) Dalam Penerapan Ekonomi Islam Melalui Perbankan Syariah di Aceh - Syamsuri Syamsuri; Nirhamna Hanif Fadillah; Amir Reza Kusuma; Jamal Jamal (ITB AAS INDONESIA Surakarta, 2021)
This article aims to analyze the dynamics of the formation of Qanun LKS (Islamic Financial Institutions) in this case implementing Islamic banking as an effort and practice of Islamic Economics in Aceh. This research is a library research using qualitative methods with descriptive-analytic analysis techniques This research found that the dynamics of the application of Qanun LKS in Aceh by running an Islamic economy through Islamic banking are solely among others, the type of Acehnese people who want to make the Islamic economic system and away from the practice of capitalism and materalism and elements of riba that are still embraced by conventional. See from the initial efforts of Islamic banking into the national banking system. First, the validity period of Law No. 10 of 1998 is referred to as the period of Islamic banking in an effort to become mainstream banking, which is to be part of the main forces among banks in the national banking system. Second, the period of Islamic banking leading the national banking system, especially in Aceh Province, is that it is necessary to apply the model of regulatory formation using a sociological approach